The relationship between motivation and employees performance at Perodua Sales Sdn Bhd / Alif Syamil Arshad and Alif Fadhli Khalid - Arshad, Alif Syamil; Khalid, Alif Fadhli (Faculty of Business and Management, 2014)
The study investigated the influence of extrinsic and intrinsic motivation on employee’s performance. Subjects for the study consisted of one hundred workers of Perodua Sales Rawang Sdn Bhd. Data for the studies were gathered through the distributions of questionnaire to the employees of Perodua Sales Sdn Bhd. The data collected were subjected to appropriate statistical analysis using Pearson Product Moment Correlation Coefficient, and all the findings were tested at 0.05 level of significance.